2020
DOI: 10.3389/fphys.2020.606740
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide and Mechano-Electrical Transduction in Cardiomyocytes

Abstract: The ability§ of the heart to adapt to changes in the mechanical environment is critical for normal cardiac physiology. The role of nitric oxide is increasingly recognized as a mediator of mechanical signaling. Produced in the heart by nitric oxide synthases, nitric oxide affects almost all mechano-transduction pathways within the cardiomyocyte, with roles mediating mechano-sensing, mechano-electric feedback (via modulation of ion channel activity), and calcium handling. As more precise experimental techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 177 publications
(230 reference statements)
0
18
0
Order By: Relevance
“…Stretch‐activated ion channels are perfectly adapted to integrate changes in the mechanical environment into an altered electrical response. Interestingly, the functional properties of some ion channels can be modified by NO (Boycott et al, 2020 ; Kazanski et al, 2011 ; Liao et al, 2006 ). Furthermore, NOS and NO production is involved in the regulation of every stage of mechanoelectrical feedback: from the initial induction of mechanical signals via integrin/cytoskeleton complexes, through the control of the action potential by modulating the activity of SACs and other ion channels, to the mediation of Ca 2+ processing underlying cardiac contraction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stretch‐activated ion channels are perfectly adapted to integrate changes in the mechanical environment into an altered electrical response. Interestingly, the functional properties of some ion channels can be modified by NO (Boycott et al, 2020 ; Kazanski et al, 2011 ; Liao et al, 2006 ). Furthermore, NOS and NO production is involved in the regulation of every stage of mechanoelectrical feedback: from the initial induction of mechanical signals via integrin/cytoskeleton complexes, through the control of the action potential by modulating the activity of SACs and other ion channels, to the mediation of Ca 2+ processing underlying cardiac contraction.…”
Section: Discussionmentioning
confidence: 99%
“…NO production increases in response to various mechanical forces, a phenomenon that is of particular importance for cardiovascular function. For example, studies using NO‐sensitive dyes have shown that stretching of ventricular cardiomyocytes induces NO release (Boycott et al, 2020 ; Shim et al, 2017 ; Suárez et al, 1999 ). In some works, 20% sustained stretch was shown to induce an increase in the [NO] in within 5 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…talin, vinculin) that are able to sense and integrate mechanical signals. It was suggested that NO stimulation of integrins then promotes NO‐mediated Ca 2+ release from the sarcoplasmic reticulum and modulates the function of L‐type Ca 2+ channels (Boycott et al., 2020). In the context of pacemaker function, this would exert a repercussion on the Ca 2+ clock and affect beat rate.…”
Section: Discussionmentioning
confidence: 99%
“…It would seem likely that this effect probably involves β3AR, given that this receptor also seems to be heavily localized to t-tubules [ 102 ] [ 103 ]. Nitric Oxide appears to be intimately connected to mechano-electric coupling within cardiomyocytes [ 104 ]. Unlike eNOS, nNOS can be directly activated by stretch or catecholamines in cardiac myocytes, and local NO-CaMKII by βAR [ 105 ].…”
Section: The ‘Structural’ Modulation Of Cardiac Electrophysiology By β-Adrenergic Receptorsmentioning
confidence: 99%